Digital Solution Layanan Hasil Penelitian Civitas Akademika Universitas Lambung Mangkurat - Fahruraji Fahruraji; Noorliana Noorliana; Asnah Asnah (THE LIGHT : Journal of Librarianship and Information Science, 2021)
The purpose of the research are To understand the library system that is being used by UPT Library Lambung Mangkurat University Banjarmasin; Identify the problems in library; Produce recommendation about digital library information system as a process to enhance the effectiveness and the efficiency. Qualitative method with an action research approachment is being used in this research are interview, observation and documentation. Data collected then analyzed in descriptive qualitative approach. This research shows how conventional system applied in UPT Library Lambung Mangkurat University Banjarmasin library leads to ineffectiveness and inefficiency that affects the user and operator; There are many negative sides which are limited time access, longer book-searching and borrowing process, human error in recording, and many others; Thus, the researcher gives a solution in a form of digital library website in order to lift the effectiveness and efficiency in every single library activity. Based on the result, it is known that library system that is being used in UPT Library Lambung Mangkurat University Banjarmasin still conventional. There are several weaknesses such as limited time acces, ineffective and inefficient in book-searching process, transaction, and recording. Information system by solusion, digital library using digital library website is a correct option to prevent any problem exist in current library system.